Phylogeography of Bacillus anthracis in the Country of Georgia Shows Evidence of Population Structuring and Is Dissimilar to Other Regional Genotypes - Khmaladze, Ekaterine (Public Library of Science, 2014)
Sequence analyses and subtyping of Bacillus anthracis strains from Georgia reveal a single distinct lineage (Aust94) that is ecologically established. Phylogeographic analysis and comparisons to a global collection reveals a clade that is mostly restricted to Georgia. Within this clade, many groups are found around the country, however at least one subclade is only found in the eastern part. This pattern suggests that dispersal into and out of Georgia has been rare and despite historical dispersion within the country, for at least for one lineage, current spread is limited.